TRANSFORMASI RUANG LITERASI INTERAKTIF: STRATEGI DIGITALISASI PERPUSTAKAAN DAN IMPLEMENTASI TEKNOLOGI AI-VR DALAM MENDUKUNG MINAT BACA SISWA ERA DIGITAL - Rahma Rizki Apriliani; Titania Nelvi Savira; Najwa Putri Ramadhani; Zahrotul Munawwaroh (STKIP Pesisir Selatan, 2026)
The development of digital technology has brought significant changes in students' learning patterns and reading interests, requiring schools to make strategic transformations in library management. This study aims to analyze the transformation of interactive literacy spaces through library digitization and the implementation of Artificial Intelligence (AI) and Virtual Reality (VR) technologies in supporting the increase of students' reading interest in the digital era. The study uses a qualitative approach with a literature review method of 52 primary sources obtained from reputable national and international journals, scientific proceedings, and relevant dissertations. Data analysis was conducted using content analysis techniques with thematic coding to identify patterns, concepts, and key findings. The results show that library digitization serves as the foundation for literacy accessibility, AI-based personalization increases the relevance and engagement of students with reading materials, while the immersive VR experience is able to convert passive reading interest into active interest. The synthesis of findings gave birth to the Interactive Literacy Space (RLI) Framework, which consists of four main pillars: hybrid digital access, AI personalization, VR immersion, and collaborative communities. The integration of these four pillars has been proven to contribute significantly to the holistic improvement of students' reading interest.